Analysis of Factors Influencing Mothers' Interest in Using IUD Contraception at PKM Kemuningsari Kidul - Painem, Painem; Safitri, Rani (Sean Institute, 2025)
The issue of low use of long-term contraception such as IUD is still a challenge in the program for Family Planning (KB) in Indonesia. This study's goal is to investigate the impact of knowledge, attitudes, and husband's support on mothers' interest in using IUD contraception at work ​​Kemuningsari Kidul Health Center. This study used a using a cross-sectional design and a quantitative descriptive analytical method and involved 30 fertile mothers selected through purposive sampling techniques. The tool that was employed was a closed survey that underwent validity and reliability testing. Data analysis was carried out using SPSS version 27, including normality, homogeneity, multicollinearity, heteroscedasticity, testing for hypotheses and multiple linear regression. The results showed that attitudes and knowledge had a significant effect on mothers' interest in using IUDs (p <0.05), while husband's support had no significant effect (p>0.05). These findings indicate the importance of increasing education and correct information to encourage mothers' interest in choosing IUD contraception as a long-term family planning method.